An Integrative Literature Review of Basal-Bolus Insulin versus Sliding-Scale Insulin for Glycemic Management in the Hospitalized Non-Critically Ill Type 2 Diabetic Patient - HERR, Lindy; THIAMWONG, Ladda (Walailak Journal of Science and Technology (WJST), 2018)
Diabetes is an increasingly common chronic disease that affects the body’s normal ability to control blood glucose levels due to impaired use of the hormone insulin. It is estimated that one out of every 4 adults who are hospitalized also have a diagnosis of diabetes. Diabetic inpatients face unique challenges in regards to managing their blood glucose while hospitalized due to the physiological stress of acute illness. Unfortunately, those who experience inadequate blood glucose management in the hospital are at an increased risk for poor patient outcomes, such as infection, increased length of stay, and death. There are multiple medications used to regulate blood sugar levels; however, the most commonly prescribed treatment for inpatients is the traditional sliding-scale regimen followed by the basal-bolus insulin regimen. An integrated literature review was conducted to determine if basal-bolus insulin is more effective than sliding-scale insulin in managing blood glucose levels of non-critically ill diabetic inpatients. Four well-known databases were searched and 5 relevant quantitative research articles were obtained and analyzed. The majority of the evidence supports basal-bolus insulin as the most effective treatment for managing blood glucose and preventing hyperglycemia without increasing the risk for hypoglycemia. Health care providers should order basal-bolus insulin accordingly in order to improve patient outcomes. Future research that questions why sliding-scale insulin is still widely prescribed may identify barriers related to ordering basal-bolus insulin and assist in decreasing related adverse events.